What Is Social Media For?: A Case Study of Social Media Use and Its Effects on Student Achievement - Yonatan Tambing Bontong; Martha Betaubun; Jori Lahinda; Kristian Paruty Lewier (Edumaspul: Jurnal Pendidikan, 2023)
Social Media is a communication tool or information that allows users to have conversations, exchange information or express ideas. But this social media has become a very frightening scourge for some students, especially those who abuse social media not for the sake of learning. Social media is very influential for students to support learning achievement. Therefore, the purpose of this study is to see the influence / impact of the use of social media on student achievement. This study uses a quantitative research design, by applying normality and correlation tests to each variable. In this study there were 25 class XI students from SMK Negeri 2 Tourism Merauke, South Papua who were the subjects of the study. Data collection, carried out using observation and questionnaires. As a result of research, the use of Social Media such as Instagram, Facebook, Twitter, YouTube, WhatsApp is proven to affect student achievement. However, it depends on the goals of each student, if users use it positively it will have a good impact on student learning achievement, but on the contrary if it is used just by playing and cannot divide time to learn then it is likely to have a bad impact on student learning achievement.